Synthetic Routes to Thiol‐Functionalized Organic Semiconductors for Molecular and Organic Electronics. Issue 2 (16th November 2016) - Operamolla, Alessandra; Punzi, Angela; Farinola, Gianluca M.
Abstract: Over the few last decades, the potential of using thiol functionalities to induce the self‐assembly of various kinds of molecules on metal surfaces has been widely demonstrated. In particular, π‐conjugated molecules can undergo self‐assembly on metallic surfaces to create electroactive supramolecular layers, which have found important applications in organic and molecular electronics. For this reason, the synthesis of thiol‐functionalized conjugated molecules has been the object of extensive research and many routes have been developed for their synthesis. This Focus Review provides an overview of the state‐of‐the‐art methods for the syntheses of organic semiconductors that are decorated with pendant thiol groups for applications in self‐assembly and molecular and organic electronics. Particular attention is given to synthetic strategies based on organometallic cross‐coupling reactions for the preparation of compounds with extended conjugation. Abstract : S Club : This Focus Review offers an overview of the state‐of‐the‐art methods for the preparation of organic semiconductors that are decorated with pendant thiol groups for applications in self‐assembly and molecular and organic electronics. Particular attention is given to synthetic strategies based on organometallic cross‐coupling reactions for the preparation of compounds with extended conjugation.